Republic of San Marino : 2021 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for the Republic of San Marino. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2021)
San Marino entered the pandemic with substantial vulnerabilities and still struggling from the consequences of the Global Financial Crisis (GFC). However, the economy has shown significant resilience supported by a timely and targeted policy response. Fiscal support was substantially scaled up after external borrowing was secured, including through a debut Eurobond. The banking system was rationalized, partly capitalized, its liquidity substantially improved, and a strategy is being adopted to address exceptionally high nonperforming loans (NPLs). Some of these measures, while effective, have increased official public debt substantially.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy